2018
DOI: 10.1038/s41598-018-35732-6
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids from Semen Cuscutae target MMP9 and promote invasion of EVT cells via Notch/AKT/MAPK signaling pathways

Abstract: Miscarriage is a common condition during pregnancy and its mechanisms remain largely unknown. Extravillous trophoblast (EVT) cell invasion is required to maintain normal pregnancy and its malfunction has been proposed as a major cause for miscarriage. Homeostasis of matrix metalloproteinase 9 (MMP9) is a key to regulate EVT cell invasion. Total flavonoids from Semen Cuscutae (TFSC) have been applied clinically used for preventing or treating miscarriage in the past. Given its potential clinical benefit on prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this study, the positive correlations among the expression levels of MNSFβ, P53, and RhoA, as well as the proliferation and migration abilities of HTR8/SVneo cells were observed, indicating that the P53-RhoA pathway might be involved in the human trophoblast cell proliferation and migration and MNSFβ might promote EVT cell proliferation and migration by activating the P53-RhoA pathway. MMP-9 plays critical roles in regulation of EVT cell invasion, and an increased MMP-9 expression was found to be accompanied with the enhanced EVT cell migration [26]. More interestingly, it was reported that simultaneously decreased expression levels of MMP9 and RhoA were detected in trophoblast cells with reduced invasion ability and MMP9 could regulate trophoblast invasion ability through Rho-family signaling [27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, the positive correlations among the expression levels of MNSFβ, P53, and RhoA, as well as the proliferation and migration abilities of HTR8/SVneo cells were observed, indicating that the P53-RhoA pathway might be involved in the human trophoblast cell proliferation and migration and MNSFβ might promote EVT cell proliferation and migration by activating the P53-RhoA pathway. MMP-9 plays critical roles in regulation of EVT cell invasion, and an increased MMP-9 expression was found to be accompanied with the enhanced EVT cell migration [26]. More interestingly, it was reported that simultaneously decreased expression levels of MMP9 and RhoA were detected in trophoblast cells with reduced invasion ability and MMP9 could regulate trophoblast invasion ability through Rho-family signaling [27].…”
Section: Discussionmentioning
confidence: 97%
“…MMP-9 plays critical roles in regulation of EVT cell invasion, and an increased MMP-9 expression was found to be accompanied with the enhanced EVT cell migration [26]. More interestingly, it was reported that simultaneously decreased expression levels of MMP9 and RhoA were detected in trophoblast cells with reduced invasion ability and MMP9 could regulate trophoblast invasion ability through Rho-family signaling [27].…”
Section: Discussionmentioning
confidence: 99%
“…(Tu Si Zi) are flavonoids, which can increase estrogen receptor expression in the hippocampus, hypothalamus, and pituitary as well as luteinizing hormone receptor expression in the ovaries ( Ke and Duan, 2013 ). Recent studies have reported that these flavonoids can promote the migration and invasion of extravillous trophoblast cells by increasing matrix metalloproteinase 9 (MMP9) expression and prevent miscarriage by activating Notch, AKT, and mitogen-activated protein kinase (MAPK) signaling pathways ( Gao et al, 2018 ). Previous research has shown that these herbs also nourish the kidneys and have similar effects to those of endocrine hormones by acting directly on the ovaries and regulating the hypothalamic-pituitary-ovarian axis to prevent miscarriage ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shennong's Classic of Materia Medica recorded it as an upper-grade drug. Modern studies have indicated that CS contains flavonoids, polysaccharides, volatile oils, alkaloids, steroids, lignans, and so on; moreover, flavonoids and polysaccharides are the major bioactive components among them (Gao et al, 2018(Gao et al, , 2020Yang et al, 2017;Zhang et al, 2019). Currently, CS has demonstrated many pharmacological functions and biological activities, for instance, antioxidation effect (Lin et al, 2018;Szeto et al, 2012), anti-inflammatory effect (Liao et al, 2014), hepatoprotective activity (Yen et al, 2007(Yen et al, , 2008, and reversal of hormone levels (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%